Electrochemical Generation of ROS in Ionic Liquid for the Degradation of Lignin Model Compound. Issue 11 (24th August 2018) - Wang, Lei; Liu, Shuangyan; Jiang, Haomin; Chen, Yueying; Wang, Linan; Duan, Guoyi; Sun, Yanzhi; Chen, Yongmei; Wan, Pingyu
Abstract : p -benzyloxyl phenol (PBP), as a lignin model compound, was electrochemically degraded in [BMIM]BF4 ionic liquid (IL) using an oxygen reduction reaction (ORR) cathode. The utilization of this kind of aprotic IL made it possible to identify which kind of reactive oxygen species (ROS) played an important role in the electrochemical depolymerization of lignin. Electrochemical study confirmed that superoxide radical (·O2 − ), the one-electron reductive product of dioxygen, is the main resultant of ORR in [BMIM]BF4 . However, the generated ·O2 − radical transformed into hydroperoxyl radical (·OOH) in the presence of protons donated by PBP, and then received one more electron to form H2 O2, which then attacked and broke down the alkyl-O-aryl bonds in PBP molecules. The continuous electrolysis of PBP in [BMIM]BF4 provided indirect evidence to reveal that the in situ generated H2 O2 on ORR cathode was responsible for the cleavage of ether bonds in PBP.